The Effects of BungeeSkate[superscript]TM Training on Measures of On-Ice Acceleration and Speed - Cook, Mitch; Kaatz, Rob; Auner, Kelly; Matteson, Kaelyn; Emberts, Talisa; Muller, Emily (My University, 2012)
Previous research has stated that dry land sled pulling trains first step quickness in hockey players. Further research has demonstrated that off-ice horizontal training (sled pull, parachute, etc.) relates well to on-ice acceleration and speed. However, there is limited literature pertaining to on-ice resistance training that aims to enhance speed and acceleration in hockey players. The purpose of the present study was to determine if on-ice BungeeSkate training will improve on-ice speed and acceleration in youth hockey players.
Color poster with text, photographs, figures, tables, and graphs.
Keywords: BungeeSkate; Physical education and training--Physiological aspects; Speed--Measurement; Hockey for children; Acceleration (Mechanics)--Measurement; Posters